The Influence of Principal Leadership Style And Work Ethic A Towards Teacher Professionalism - Harlina, Sri; Harapan, Edy; Tahrun (Jurnal Pendidikan Tambusai, 2021)
This study aims to analyze and describe: 1) the influence of the principal's leadership style on teacher professionalism, 2) the effect of work ethic on teacher professionalism, 3) the influence of head leadership style and work ethic on teacher professionalism. This research uses quantitative methods. The results of the study state that: 1) there is an influence of the Principal's Leadership Style on Teacher Professionalism; 2) there is an influence of Work Ethics on Teacher Professionalism; and 3) there is an influence between Principal Leadership Style and Work Ethic jointly on Teacher Professionalism.